HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN PENGETAHUAN TENTANG PIJAT OKSITOSIN - Ayuningtyas, Beby Yohana Okta; Oktanasari, Wiji (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The healthiest diet for babies to promote healthy growth and development is breast milk (ASI), according to the Ministry of Health (2025). Babies receive the most comprehensive nourishment from breast milk. Breastfeeding exclusively is consuming just breast milk for six months, with the exception of vitamins, minerals, and prescription drugs. Fifty percent of women worldwide are exclusively nursing. 82.3% of Kalibagor's population exclusively breastfeeds (Banyumas Health Office Profile, 2024). Exclusive breastfeeding is frequently associated with nipple pain, breast engorgement, mastitis, and breast abscesses. To increase the success rate of exclusive breastfeeding coverage, therefore, measures must be taken to overcome breastfeeding obstacles, such as oxytocin massage. Breast milk release may be improved by oxytocin massage. Raising pregnant women's awareness of oxytocin massage has the potential to improve social conduct. This study aims to determine the relationship between oxytocin massage knowledge and personal characteristics. Thirty pregnant women who were enrolled in a prenatal class at the Kaliori Community Health Center in Kalibagor made up the study sample. Total sampling was the method of sample that was employed. The concept of oxytocin massage, its advantages, efficacy, timing, factors influencing the release of the oxytocin hormone, factors impacting the success of oxytocin massage, and the processes involved in the massage were all covered in the oxytocin massage knowledge quiz. According to the chi-square test results, the p-value was less than 0.05. Individual characteristics such as age, occupation, education, and parity were significantly associated with pregnant women's knowledge of oxytocin massage (0.001; 0.000; 0.004; 0.000).Keywords: Age, education, parity, knowledge, oxytocin massage